Using Social Media to Disseminate Effective Pain Treatments for Newborns During Needle-Related Painful Procedures in China. Issue 4 (October 2021) - Hu, Jiale; Xue, Feng; Zhou, Yiyan; Liu, Yuxiao; Li, Qingge; Deng, Jun; Harrison, Denise
Abstract : Social media has become a powerful approach to disseminating evidence to knowledge users. The BSweet2Babies video was developed in multiple languages showing the effectiveness of sweet solutions, skin-to-skin care, and breastfeeding during newborn painful procedures. This study aimed to disseminate the BSweet2Babies video in Chinese through social media platform of WeChat in China; evaluate the reach, acceptability, and recommendation of the video; and assess viewers' previous knowledge and experience of using the 3 strategies and intention to use these strategies in the future. Multiple dissemination strategies were used to maximize views for a 6-month dissemination period. The video received 19 812 views, 4306 "thumbs, " and 671 participants completed surveys. Of the survey respondents, 393 were parents. Most respondents did not know these strategies and did not use or help parents use any of them. More healthcare professionals than parents intended to use or advocate for sweet solutions and breastfeeding. More healthcare professionals rated that the 3 strategies were easy to apply in real-life situations, but more parents evaluated that the length of the video was too long. Social media in China can be a promising approach to disseminating evidence on neonatal procedural pain treatments to healthcare professionals and the public.